Prophylactic Antiepileptics and Seizure Incidence Following Subarachnoid Hemorrhage: A Propensity Score–Matched Analysis. Issue 7 (July 2016) - Panczykowski, David; Pease, Matthew; Zhao, Yin; Weiner, Gregory; Ares, William; Crago, Elizabeth; Jankowitz, Brian; Ducruet, Andrew F.
Abstract : Background and Purpose—: The utility of prophylactic antiepileptic drug (AED) administration after spontaneous subarachnoid hemorrhage remains controversial. AEDs have not clearly been associated with a reduction in seizure incidence and have been associated with both neurological worsening and delayed functional recovery in this setting. Methods—: We retrospectively analyzed a prospectively collected database of subarachnoid hemorrhage patients admitted to our institution between 2005 and 2010. Between 2005 and 2007, all patients received prophylactic AEDs upon admission. After 2007, no patients received prophylactic AEDs or had AEDs immediately discontinued if initiated at an outside hospital. A propensity score–matched analysis was then performed to compare the development of clinical and electrographic seizures in these 2 populations. Results—: Three hundred and fifty three patients with spontaneous subarachnoid hemorrhage were analyzed, 43% of whom were treated with prophylactic AEDs upon admission. Overall, 10% of patients suffered clinical and electrographic seizures, most frequently occurring within 24 hours of ictus (47%). The incidence of seizures did not vary significantly based on the use of prophylactic AEDs (11 versus 8%; P =0.33). Propensity score–matched analyses suggest that patients receiving prophylactic AEDs had a similar likelihood of suffering seizures as those who did not ( P =0.49). Conclusions—: Propensity score–matched analysis suggests that prophylactic AEDs do not significantly reduce the risk of seizure occurrence in patients with spontaneous subarachnoid hemorrhage.